Effect of Incorporating Sustainability Strategies into Building Maintenance Practices - Ezebuilo, Kenneth Chidiebere; OMENYI, Chioma Anastasia; Awuzie, Obinna Davidsyn (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2025)
The study analyzed     incorporating sustainability strategies into building maintenance practices.  This study adopted a surveys research style. The research population comprises of students, staff of works department and physical planning units in Nnamdi Azikiwe University Awka. cluster sampling technique was adopted for the study. The instrument used was a structured questionnaire. To ensure the validity of data collection instrument, the questionnaires was submitted to the researcher’s supervisor who assessed the content and structure. The test for reliability of the instrument was done using the Cronbach’s Alpha. To ensure the validity of data collection instrument, the questionnaires was submitted to the researcher’s supervisor who assessed the content and structure. The study showed that maintaining same level of service, that is extra cost of repair and replacement are reduced (1st) has the most severe effect on incorporating sustainability into building maintenance practices in Nnamdi Azikiwe University Awka. It was concluded that sustainable maintenance not only supports regulatory compliance but also contributes to broader climate goals and corporate social responsibility. One of the recommendations made was that the best sustainability strategies suitable for the maintenance of buildings in the study area should be adopted, as it will prolong the usefulness and effective life of buildings in the study area.